2009
DOI: 10.1002/art.24842
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 is involved in resolution of inflammation in proteoglycan‐induced arthritis

Abstract: Objective. CCR5 and its ligands (CCL3, CCL4, and CCL5) may play a role in inflammatory cell recruitment into the joint. However, it was recently reported that CCR5 on T cells and neutrophils acts as a decoy receptor for CCL3 and CCL5 to assist in the resolution of inflammation. The aim of this study was to determine whether CCR5 functions as a proinflammatory or antiinflammatory mediator in arthritis, by examining the role of CCR5 in proteoglycan (PG)-induced arthritis (PGIA). Methods. Arthritis was induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…Our findings suggest that cartilage degeneration can proceed without significant synovitis. Despite the evidence for the pro-inflammatory role of CCR5, several studies suggest its anti-inflammatory role 27,43 . Therefore, we suggest that further mechanistic studies are needed to investigate the roles of CCR5 and its ligands in modulating changes in cartilage following a traumatic joint injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that cartilage degeneration can proceed without significant synovitis. Despite the evidence for the pro-inflammatory role of CCR5, several studies suggest its anti-inflammatory role 27,43 . Therefore, we suggest that further mechanistic studies are needed to investigate the roles of CCR5 and its ligands in modulating changes in cartilage following a traumatic joint injury.…”
Section: Discussionmentioning
confidence: 99%
“…We are interested in C–C chemokine receptor type 5 (CCR5) for the following specific reasons: (1) CCR5 has been identified to serve as a functional receptor for several inflammatory C–C-chemokines, including macrophage inflammatory protein 1α (MIP-1α, also called C–C motif ligand 3 or CCL3), MIP-1β (CCL4), and RANTES (regulated on activation, normal T cell expressed and secreted, also called CCL5) 9,11,12 , (2) in vitro studies in our laboratory have shown that levels of many chemokines including CCL3, C–C motif ligand 3 like 1 (CCL3L1) and CCL4 are elevated in human articular chondrocytes in response to the pro-inflammatory cytokine interleukin (IL)-1β and the adipokine resistin 1315 , (3) CCR5 and its ligands maintain the inflammatory process in rat adjuvant-induced arthritis whereas blocking of CCR5 has resulted in reduced joint destruction 1618 , (4) CCR5 has been reported to be expressed in normal and OA chondrocytes 14,19,20 and its expression is elevated in OA chondrocytes 14,21 as well as after RANTES stimulation 19 , (5) CCR5 has been found in synovial fluid and synovial tissues of patients with rheumatoid arthritis 2224 as well as accumulation of CCR5 + T cells in the inflamed joint 25,26 and finally, (6) CCR5 plays an important role in the clearance of pro-inflammatory chemokines to resolve inflammation 27 . Despite the important role of chemokines and chemokine receptors in rheumatoid arthritis, direct evidence for the role of CCR5 in post-traumatic OA is not available.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of CCR5 in the surface of the immune system cells helps their migration to tissues, promoting inflammation. On the other hand, CCR5 can also be involved in resolution of inflammation through some possible mechanisms [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 ligands are CCL3 (macrophage inflammatory protein (MIP-1a)), CCL4 (MIP-1b), CCL5 (regulated on activation normal T cell expressed and presumably secreted (RANTES)) and CCL8 (monocyte chemoattractant protein (MCP-2)), and the receptor is mainly expressed on the surface of cells that participate in inflammatory processes, such as lymphocytes, activated Th1 memory cells, monocytes, macrophages, dendritic cells and neutrophils. [3][4][5][6] The CCR5 gene is located on chromosome 3p21.3-p24. Its polymorphic variant CCR5delta32 has a 32 bp deletion (dbSNP: rs333), which generates a truncated protein that does not reach the cell surface.…”
Section: Introductionmentioning
confidence: 99%